Return passes in handball - Sibila, M. (2010)
Return passes are also an important tactical element of offence in some other sport games. They are very common in football where players use return both transversal and longitudinal passes to break the defence. In our opinion, the use of return passes should also become more frequent in handball. This could be achieved, among other things, by presenting the tactical advantages of return passes to younger age categories. The return pass basics can be taught to the youngest categories of players as soon as they have mastered the technique of moving within the court, passing and receiving the ball as well as shooting at the goal.